PANCASILA SEBAGAI STAATSFUNDAMENTALNORM INDONESIA DALAM PEMBENTUKAN HUKUM NASIONAL (Perspektif Undang-Undang Cipta Kerja Nomor 11 Tahun 2020 Tentang Cipta Kerja) - Novrizal, Rahmat Irwan; Marzuki, Marzuki; Nasution, Mirza (Jurnal Ilmiah METADATA, 2021)
Pancasila is said to be normative, because Pancasila serves as the base and ideal prerequisite in every formation of positive law. The things that underlie the controversy over the formulation and formation and ratification of Law Number 11 of 2020 concerning Job Creation are that many ignore the welfare of workers through policy revisions that favor the owners of capital. The formulation of the problem in this thesis is how the things that underlie the controversy over the formulation and formation and ratification of Law Number 11 of 2020 concerning Job Creation, how to protect the rights of workers in Law Number 11 of 2020 concerning Job Creation, how Pancasila as a staatsfundamentalnorm in the formation of national law, especially in the formation of the Job Creation Act. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that the protection of workers' rights in Law Number 11 of 2020 concerning Job Creation is related to the articles governing Manpower which are summarized in Article 81, so it has not accommodated guarantees of rights for workers. Pancasila as a staatsfundamental norm in the formation of national law, especially in the formation of the Job Creation Act is to regulate and be able to formulate legislation, national legal politics must refer to Pancasila which is based on morals and religion, respects and protects human rights without discrimination and racist, uniting all elements of the nation with all their primordial ties and placing power under their control and building social justice for all Indonesian people.